Design and Simulation of Bridgeless Cuk Converter as Electric Vehicle Battery Charger - Sabatino, Demas; Ashraf Ahmad, Mohd (Universitas Muhammadiyah Surakarta, 2025)
Two-wheeled electric vehicles in Indonesia have special specifications with SNI standards on rechargeable battery components. To recharge the battery with a household PLN power source, a charger device is required that meets the input and output specifications. In this study I will design and simulate a battery charger device with an output voltage specification of 72V and a maximum current of 3A. The charger device uses a bridgeless cuk converter topology with an input voltage that adjusts to 220Vrms AC household electricity. By using the specifications on the input and output, the calculation in the design produces a nominal duty cycle value of 18.8% at a frequency of 100kHz, and the component values . The first simulation was conducted with a fixed duty cycle of 18.8% which produced a full-wave sinusoidal output signal where the maximum voltage was -70.5 V and the average voltage was -45 V, the maximum current was -2.93 A and the average current was -1.87 A. The power efficiency of the first simulation result was 96.2%. The second simulation was conducted with a duty cycle control in the form of a comparator from the saw signal and the output voltage of the cuk converter. The second simulation produced a more constant signal with a maximum voltage of -100 V and an average voltage of -73 V, a maximum current of 4 A and an average current of -3.05 A. The power efficiency of the second simulation result was 96.99%.